2019
DOI: 10.1029/2018ja026354
|View full text |Cite
|
Sign up to set email alerts
|

FORESAIL‐1 CubeSat Mission to Measure Radiation Belt Losses and Demonstrate Deorbiting

Abstract: Today, the near‐Earth space is facing a paradigm change as the number of new spacecraft is literally skyrocketing. Increasing numbers of small satellites threaten the sustainable use of space, as without removal, space debris will eventually make certain critical orbits unusable. A central factor affecting small spacecraft health and leading to debris is the radiation environment, which is unpredictable due to an incomplete understanding of the near‐Earth radiation environment itself and its variability driven… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 72 publications
0
22
0
Order By: Relevance
“…It is evident from the executive summary of ISS, which encapsulates the achievements of innovative research on the orbiting laboratory that had created a positive impact on the quality of life on Earth and the future scope of the interdisciplinary researches globally for creating an impact on scientific advancement. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Herein we conduct theoretical studies for providing the proof of the concept of space debris recycling and energy conversion system in a microgravity environment with an intention to carry out real-time experiments in the space platform through the multinational collaboration with wide scope and benefits to humanity. The emerging application of outer space for the progression of the standard of living and quest for wisdom has led to the growth of space debris or space junk in orbits where the large number of satellites is operational.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is evident from the executive summary of ISS, which encapsulates the achievements of innovative research on the orbiting laboratory that had created a positive impact on the quality of life on Earth and the future scope of the interdisciplinary researches globally for creating an impact on scientific advancement. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Herein we conduct theoretical studies for providing the proof of the concept of space debris recycling and energy conversion system in a microgravity environment with an intention to carry out real-time experiments in the space platform through the multinational collaboration with wide scope and benefits to humanity. The emerging application of outer space for the progression of the standard of living and quest for wisdom has led to the growth of space debris or space junk in orbits where the large number of satellites is operational.…”
Section: Introductionmentioning
confidence: 99%
“…Various reports and industrial engineering data on the usefulness of the prevailing debris extenuation methods are inadequate for a realistic conclusion. [4][5][6][7][8][9][10][11][12][13][14][15][16] The present trend of global space activities indicates that in the ensuing decades' huge volumes of space debris will be in orbit and there is a need to update the debris alleviation normal exercises to stimulate competent and active practices to better abate the risks from space debris for the benign maneuvers of future space missions. [4][5][6][7]14 The fact is that even if all the upcoming space launches are called off, the space debris that already exists will be tendering threats for numerous decades to come before all of them re-enter the earth and burn off.…”
Section: Introductionmentioning
confidence: 99%
“…Literature review reveals that through fundamental research and development a few products and services derived from space station activities are entering the souk and furthering healthy and peaceful life on Earth [1], which is motivating us to propose more challenging research in ISS. It is evident from the executive summary of ISS, which encapsulates the achievements of innovative research on the orbiting laboratory that had created a positive impact on the quality of life on Earth and the future scope of the interdisciplinary researches globally for creating an impact on scientific advancement [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Herein we conduct theoretical studies for providing the proof of the concept of space debris recycling and energy conversion system in a microgravity environment with an intention to carry out real-time experiments in the space platform through the multi-national collaboration with wide scope and benefits to humanity.…”
Section: Introductionmentioning
confidence: 99%
“…The growing utilization of outer space for the advancement of the standard of living and hunt for wisdom has led to the accretion of space debris or space junk in high-density satellites orbits. Various reports and industrial engineering data on the usefulness of the prevailing debris extenuation methods are inadequate for a realistic conclusion [4][5][6][7][8][9][10][11][12][13][14][15][16]. J.-C. Liou et al [4][5][6][7][8] reported that as the space debris volume remains to rise over time due to the global space activities in recent years, there is a need to update the debris alleviation normal exercises to stimulate competent and active practices to better abate the risks from space debris for the benign manoeuvres of future space missions.…”
Section: Introductionmentioning
confidence: 99%
“…Vlasiator (http://www.physics.helsinki. fi/vlasiator/) is distributed under the GPL-2 open source license (Palmroth et al, 2019). To learn more, see von Alfthan et al (2020).…”
mentioning
confidence: 99%